Mewujudkan Akuntabilitas Organisasi Sektor Publik Melalui Audit Kinerja - Susanty, Yunni (Pusat Pembelajaran dan Strategi Kebijakan Talenta Aparatur Sipil Negara Nasional, 2008)
During the time, public sector is often assessed as the den of ineficiency, extravagance, and fun leakage. Therefore, an audital developmentation is required to be conducted as on existing openness and accountability to society. One of them is by extending an audit coverage, not only in fanancial auditing but rather strengthen in an execution to make an audit of the performance. A public accountability sector can be existed if performance audit earn the implementation manifestly in governance management.